Properties roughness of sand papers and layers of shellac on acacia mangium wood / Nik Mohd Izwan Abdullah - Abdullah, Nik Mohd Izwan (2014)
Finishing is the final process in the manufacture of furniture. But, it is the most important process that will determine the value of the furniture. Acacia Mangium wood was among the most famous wood used to make furniture. The purpose of this study was to investigate the effect of the roughness of sandpaper and different layers of shellac on the wood of Acacia Mangium. There are three tests used in this study including pencil hardness, surface roughness, and scratch test. For the roughness of sandpaper are used, there are three types, namely 120, 240 and 320 micrometers. However, the roughness of sandpaper 120 produces the best results and followed sandpaper 240 and 320. During this test showed significant results with each other. Moreover, the difference shellac coatings used are 1, 2 and 3 layers. After performing the test, it is found that 3 layers give the best durability for wood and followed by 2 and 1 layer. However, 2 and 3 layer does not affect significantly the pencil hardness test.